2008
DOI: 10.1037/0022-3514.95.1.18
|View full text |Cite
|
Sign up to set email alerts
|

God and the government: Testing a compensatory control mechanism for the support of external systems.

Abstract: The authors propose that the high levels of support often observed for governmental and religious systems can be explained, in part, as a means of coping with the threat posed by chronically or situationally fluctuating levels of perceived personal control. Three experiments demonstrated a causal relation between lowered perceptions of personal control and the defense of external systems, including increased beliefs in the existence of a controlling God (Studies 1 and 2) and defense of the overarching socio-po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

51
876
9
21

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 653 publications
(957 citation statements)
references
References 104 publications
(126 reference statements)
51
876
9
21
Order By: Relevance
“…Compensatory control theory proposes that one reason why desire for personal control is so encompassing is because it is a subgoal of a larger motivation to see the world as structured, orderly, and predictable (Kay, Gaucher, Napier, Callan, & Laurin, 2008;Kay, Whitson, Gaucher, & Galinsky, 2009). That is, the notion that one's life circumstances might be randomly determined often provokes anxiety (e.g., Glass, Singer, & Friedman, 1969;Laurin, Kay, & Moscovitch, 2008;Pennebaker & Stone, 2004) and belief that one has personal control is an especially effective means of affirming that the world is structured rather than random.…”
Section: Compensatory Controlmentioning
confidence: 99%
See 3 more Smart Citations
“…Compensatory control theory proposes that one reason why desire for personal control is so encompassing is because it is a subgoal of a larger motivation to see the world as structured, orderly, and predictable (Kay, Gaucher, Napier, Callan, & Laurin, 2008;Kay, Whitson, Gaucher, & Galinsky, 2009). That is, the notion that one's life circumstances might be randomly determined often provokes anxiety (e.g., Glass, Singer, & Friedman, 1969;Laurin, Kay, & Moscovitch, 2008;Pennebaker & Stone, 2004) and belief that one has personal control is an especially effective means of affirming that the world is structured rather than random.…”
Section: Compensatory Controlmentioning
confidence: 99%
“…As an analogy (see Kay et al, 2008), imagine a glass that, when full, represents an individual's preferred level of structure. Under typical circumstances, people may be able to maintain a full glass by perceiving personal control over events.…”
Section: Compensatory Controlmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, in Study 4 I examined how the element of perceived control in relationships contributes to the support of committed relationship ideology. In past research control has been shown to be an important factor in the support of societal systems such as religion and the government (e.g., Kay et al, 2008). For relationship contexts, I defined control as the perceived structure and order that relationships can provide.…”
Section: Limitationsmentioning
confidence: 99%